STUDI HABITAT MONYET BOTI (Macaca tonkeana) DI HUTAN LINDUNG DESA SANGGINORA KECAMATAN POSO PESISIR SELATAN KABUPATEN POSO - Pombu, Dikson; Labiro, Elhayat; Malik, Adam (Warta Rimba, 2014)
Few studies have explicitly determine the habitat of monyet boti (Macaca tonkeana) in nature reserve areas in Central Sulawesi. The outcome of this research is to give basic information concerning the conservation and captivation of Macaca tonkeana as an endemic and endangered animal in Sulawesi. Here in, we reported upon the results of the habitat of Macaca tonkeana in protection forest area, Sangginora village, Poso Pesisir Selatan district, Poso, Central Sulawesi.The study was conducted on March through May 2014. Five sample plots were made by the size of 20 x 20 m. Ploting was done by purposive sampling method. Hence vegetation date were analysed to determine the density, frequency, dominant, and Importance Value Index. The results showed that there were 40 plant species comprising 25 families in this area. Four plants species were used by Macaca tonkeana as food sources. The highest important value index (IVI) was achieved by Ficus sp (45,43%), while the lowest Important value index was achieved by Melochia umbellate and Rapanea spec (6,75%). Nunu (Ficus sp) is an important source of food, especially the fruit, parts of the plant are eaten fruit and leaves. Further more, the abiotic condition of the habitat including; temperature (24ºC-27ºC) and relative humidity (69%-72%) and located at 747 m asl. Keywords: Habitat, Macaca tonkeana, Protection forest, Important Value Index.